Teachers' conceptions towards the usage of authentic materials to teach listening comprehension in the ESL classroom (IR) - Gunavathy Krishnan (2009)
Listening, the most frequently used form of language skill, plays a significant role in daily communication and educational process. In spite of its importance, listening ability development has received only slight emphasis in language instruction. The fundamental purpose of this study was to examine the teachers' conception towards the usage of authentic materials to teach listening comprehension skills in ESL classroom. This descriptive study examined how the use of authentic input in an ESL classroom eased and/or impeded students' learning in English-language listening. In conjunction with the primary objective, the study also determined the influences of the use of authentic materials on listening ability in students of English as a second language and the influences of using authentic materials on ESL students' attitudes towards learning English. The analysis of data obtained from interviews with teachers revealed that the use of authentic listening materials in the ESL classroom helped increase students' comfort level and self confidence to listen to the target language. The study also discovered that implementing authentic materials in ESL classroom heightened the students' attitudes towards language learning. The use of authentic listening materials in ESL classroom had a positive effect on ESL students' motivation to learn the language. The major fmdings of this study suggested that authentic materials helped significantly to enhance the learners' listening comprehension skill and their motivation toward learning English. Based upon the conclusions drawn from the study, authentic materials were thus recommended to be integrated into the teaching of listening comprehension in ESL classroom. Pedagogical implications for the application of authentic materials in ESL teaching, especially suggestions for teaching listening comprehension were proposed. Finally, suggestions for future research were recommended.